2023
DOI: 10.3390/life13061363
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Associations with Keratoconus

Abstract: Keratoconus is a disease of the cornea that results in progressive steepening and thinning of the cornea and subsequent vision loss. It nearly always presents as a bilateral disease, suggesting that there is an underlying abnormality of the corneas that becomes manifest with time. However, the mechanisms underlying the development of keratoconus are largely unknown. Associations reported between keratoconus and systemic diseases are abundant in the literature, and the list of possible associations is very long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 126 publications
0
2
0
Order By: Relevance
“…In multiple studies, it has been found that the expression levels of IL1B, IL6, and TNF in the tear fluids or epithelial cells were significantly elevated in KC patients [ 23 , 31 ]. IL4, a central role in atopic diseases, was also an important risk factor for KC [ 48 ]. IL10 is another primarily anti-inflammatory cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…In multiple studies, it has been found that the expression levels of IL1B, IL6, and TNF in the tear fluids or epithelial cells were significantly elevated in KC patients [ 23 , 31 ]. IL4, a central role in atopic diseases, was also an important risk factor for KC [ 48 ]. IL10 is another primarily anti-inflammatory cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of KC is a subject still under debate [38], with the inflammatory theory being the one that has been on the rise in recent times [39], especially due to its association with ocular rubbing [40]. However, much remains to be known since genetic factors, family associations, and systemic conditions have also been related to its development [38,41]. Moreover, the proteomic and transcriptomic analysis suggested dysregulations in oxidative stress, NRF2-regulated antioxidant programs, WNT-signaling, TGF-β, ECM, and matrix metalloproteinases as possible causes of KC [38].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Diagnostics 2024, 14, 707 2 of 17 collagens I and IV and of other structural proteins is reduced in KC patients [6]. Similar molecular changes happen in connective tissue diseases and a link between Ehlers-Danlos syndrome, Marfan's syndrome, osteogenesis imperfecta and mitral valve prolapse and KC has been proposed, although, in general, the scientific evidence is weak and few studies exist on this topic [7].…”
Section: Introductionmentioning
confidence: 99%